2014
DOI: 10.4103/0976-3147.145196
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between plasma total nitric oxide levels and cerebral vasospasm and clinical outcome in patients with aneurysmal subarachnoid hemorrhage in Indian population

Abstract: Context:Cerebral vasospasm remains a major cause of morbidity and mortality in patients with aneurysmal subarachnoid hemorrhage (aSAH). Reduced bioavailability of nitric oxide has been associated with the development of cerebral vasospasm after aSAH. Such data is not available in Indian population.Aims:The objective of the study was to measure the plasma total nitric oxide (nitrite and nitrate-NOx) level in aSAH patients and healthy controls treated at a tertiary hospital in India and to investigate a possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
(39 reference statements)
0
2
0
1
Order By: Relevance
“…Interestingly, while metformin has significantly ameliorated the increase of NO x as compared to DOX group, it increased NO x level as compared to control and sitagliptin groups. It is already well known that NO may represent a double edged sword with pleotropic physiological as well as some serious deleterious effects in case of overproduction [ 32 ]. Zhang and colleagues have shown that the improvement in cardiac structure and function following metformin treatment in a rat model of ventricular hypertrophy was associated with enhanced eNOS and increased NO production [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while metformin has significantly ameliorated the increase of NO x as compared to DOX group, it increased NO x level as compared to control and sitagliptin groups. It is already well known that NO may represent a double edged sword with pleotropic physiological as well as some serious deleterious effects in case of overproduction [ 32 ]. Zhang and colleagues have shown that the improvement in cardiac structure and function following metformin treatment in a rat model of ventricular hypertrophy was associated with enhanced eNOS and increased NO production [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“… 107 (5) Reduced levels of NO are associated with increased incidence of cerebral vasospasm and poor outcome in SAH patients. 108 (6) Estrogen increases the level of NO in brain and peripheral vascular endothelial cells, and alleviates the vascular spasm after SAH. 109 (7) Progesterone reduces cerebral vasospasm induced by SAH via upregulating eNOS through Akt signaling pathway.…”
Section: N Europrotection and N Eurotoximentioning
confidence: 99%
“…В ходе реакции образуется окрашенный диазопродукт с максимумом поглощения при длине волны 548 нм. Так как реактив Грисса выявляет только нитриты, проводят реакции восстановления нитратов в нитриты с помощью либо нитратредуктазы, либо металла ванадия (III) [27,28].…”
Section: лабораторные методыunclassified